Missense mutations in exon 2 of the porcine leptin receptor gene and their associations with litter size and body weight - C. Sun; L. Wang; D. F. Jiang; B. Zhang (Czech Journal of Animal Science, 2009)
Leptin receptor (LEPR) gene is regarded as a "candidate-gene" of production traits. The aims of this study were to detect polymorphisms of exon 2 within LEPR gene and to investigate their associations with production traits, litter size and live weight in Luchuan and Large White pig breeds. For this purpose, the single nucleotide polymorphisms (SNPs) of exon 2 within LEPR were detected using the PCR-SSCP procedure and their association with litter size and live weight was also analysed in Luchuan (n = 446) and Large White pigs (n = 405). The results showed that the C155T mutation was found in exon 2 of porcine LEPR gene in analyzed populations, which caused a missense mutation (Met to Thr). The different genotypes of this locus had the effects on total number of piglets born, born alive of the first (1st) and the first to the fourth (1st-4th) litters. The individuals with allele A had a higher number of total piglets born and a higher number of born alive piglets in the first litter (P < 0.05) while the differences in birth weight, weaning weight and average daily gain were not significant among different genotypes of this locus in analyzed populations. It implies that the exon 2 (Thr/Met) mutation of LEPR gene is a potential gene marker of pig reproduction. Therefore, it can be used in the marker-assisted selection (MAS) of pig breeding work.